Outcome of microbiologically proven pneumonia by nasopharyngeal aspirate of infant attending in a tertiary care hospital (Northern International Medical College Journal, 2018)
Background : In Bangladesh, recent estimates suggests that 22% of under-five death and 13.1% of neonatal death is due to pneumonia. Its etiology usually remains unknown and problems is increasing with drug resistant infections.Objective : The aim of this study is to evaluate the outcome of microbiologically proved pneumonia of the infant by nasopharyngeal aspirate culture.Methods : This prospective study was conducted at the Department of Pediatrics and Neonatology, Addin Medical college hospital, Dhaka from January to July 2015. A total of 30 hospitalized infants of either sex with pneumonia fulfilling the WHO criteria and radiologically confirmed were enrolled in the study. Child with congenital heart disease or chronic respiratory disease, who did not give consent were excluded from the study. The study cases were divided into three groups on their final outcome as improved, not improved (prolonged hospital stay) and expired.Results : Among 30 study cases mean age was 39.7±45 days, most of them were male 19 (63%); case fatality rate was 10%. Organisms were isolated from 47.3% cases of nasopharyngeal aspirate culture, among them Gram-ve bacteria were 10 (34%), gram +ve 3 (10%) and fungal 1(3.3%). Mixed bacterial growth were 4(13%) and no growth were 12(40%) cases. Acinetobacter was found in 8 (26.7%), Coagulase negative staphylococcus 2(6.7%). Additionally, MRSA, pseudomonas and E.coli species were identified in 1 (3.3%), 1 (3.3%), and 1 (3.3%) of the cases respectively. All infant who had gram +ve 3(100%) and fungal 1(100%) growth on their nasopharyngeal culture were improved. On the other hand, among the gram –ve cases mortality rate was high 2(20%) and also required prolonged hospital stay 2(20%). Among the cases who had mixed organism 2(50%) of them were improved and 2(50%) required prolonged hospital stay. Majority of the cases were improved 10(83%) those who had no growth on their NPA culture followed by 1(8.3%) had prolonged hospitalization and 1(8.3%) was died.Conclusion : Infant with severe pneumonia having younger age were at greater risk of mortality. Gram – ve organism in nasopharyngeal aspirate culture indicated poorer outcome and required prolonged hospital stay.Northern International Medical College Journal Vol.9(1) July 2017: 267-270